207k views
0 votes
For the equation given below, evaluate y′ at the point (−2,−1).

3xy−3x−12=0.

User Geuis
by
6.0k points

1 Answer

2 votes

Answer:

Y'=3xy-3x-12

Y'=F(-2,-1)=0

Explanation:

The function of the equation at the point (-2,-1)

is where the equation make the function go to zero:

Y'=3xy-3x-12

Y'=F(-2,-1)=[3(-2)(-1)]-[3(-1)]-12

F(-2,-1)=[6]-[-6]-12

F(-2,-1)=6+6-12

F(-2,-1)=12-12

F(-2,-1)=0

Solving for y

3xy-3x-12=0

y=4/x+x

Making y=0


(4)/(x)+x=0


x^(2) =-4


x=-2

So the values make the function go to zero

User Inherited Geek
by
7.0k points